Hyper-extended rift systems in the Xisha Trough, northwestern South China Sea: Implications for extreme crustal thinning ahead of a propagating ocean. (November 2016) - Lei, Chao; Ren, Jianye
Abstract: From the apex of the NW Sub-basin of the South China Sea, we present new long-cable deep-penetration seismic profiles and deepwater drillings together with corrected seismic interpretations from previous studies. Structural mapping demonstrates that the Xisha Trough is characterized by a hyper-extended rift system that shows evidence of extremely thinned crust and rotated fault blocks. A series of NE, NEE and W-E striking listric normal faults along the Xisha Trough, which merge at depth into Moho reflection, record strongly extensional deformation. Based on the absence of an acoustic basement beneath a wedge-shaped rifted sequence, we document three diapiric magma structures exiting the Moho and penetrating into the extremely thinned continental crust, which is covered by a Cenozoic sequence. For the Xisha Trough we can demonstrate, based on seismic data and calculated fault slip rates, the faults bounding the Xisha Trough were initially formed by distributed rifting, and were reactivated and focused on faulting along the axis of the Xisha Trough. However, the peak faulting migrated along the margin strike from east to west and terminated at the apex of the Xisha Trough. One of the key processes, controlling the evolution of the Xisha Trough, is depth-dependent extension, which may arise from differential lithospheric stretching by regional dynamic lower crustal/mantle flow. Graphical abstract: Highlights: Along strike variations in the hyper-extended crustal and basin structures ahead of the V-shaped oceanic propagator. Deformation evolved from diffuse and wide to more localized deformation. Extreme crustal thinning and dynamic lower crustal/mantle flow occurred there.